Implementasi Pembiayaan Manindo Grameen Syariah dengan Akad Murabahah pada Koperasi Mitra Manindo Cabang Panyabungan - Jureid, Jureid (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Manindo Grameen Syariah (MGS) product is a non collateral financing product forKoperasi Mitra Manindo customers. It is a solution for the poor in obtaining business financing. Koperasi Mitra Manindo adopts the Grameen Bank system and combine it with a murabahah agreement to make it easier for poor women to obtain Startup Capital. This study used a qualitative approach with descriptive analysis by describing the actual information obtained from the respondents. Data collection techniques are through documentation, observation and interview with interviewess in order to produce in-depth and objective data. The results of this study conclude that in implementing Murabahah financing, Koperasi Mitra Manindo does not provide goods as Murabahah objects but provides money without using the wakalah contract as a complement to the contract. In this case, Koperasi uses a mudharabah financing scheme with a murabahah contract but it still causes damage to the contract due to the absence of object objects. Manindo Grameen Syariah financing with a murabahah contract carried out by the Manindo Mitra Cooperative is not in accordance with the murabahah principle, particularly about the object of goods (mabi '), Koperasi Mitra Manindo is supposed to act as a seller does not have goods to be traded but only provides money as business capital for its members.